The Sutton-Taylor feud : the deadliest blood feud in Texas - Parsons, Chuck (A.C. Greene series ;, 2009)
The Sutton-Taylor Feud of DeWitt, Gonzales, Karnes, and surrounding counties began shortly after the Civil War ended. The blood feud continued into the 1890s when the final court case was settled with a governmental pardon. Of all the Texas feuds, the one between the Sutton and Taylor forces lasted longer and covered more ground than any other.